Cancer Prevention - Senn, H.-J; Kapp, U. (Recent Results in Cancer Research, 2007)
This volume contains the main proceedings of the fourth international conference on "Cancer Prevention 2006," which was held during February 16-18, 2006, in St. Gallen, Switzerland. Written by international experts in the field, the book comprises a comprehensive update on the most recent developments in the upsurging fields of molecular biology and cancer genetics and their interactions with clinical epidemiology and cancer prevention at various levels: genetic/biologic predisposition and definition of high-risk groups; preclinical models and tumor prevention; prospects of surrogate endpoints and biomarkers; progress in imaging and detection of neoplastic precursor lesions; problems with Cox-2 inhibitors in tumor chemoprevention; primary and secondary prevention of gynecological, breast, gastrointestinal and genitourinary cancers. In addition, the future prospects of cancer chemoprevention are discussed.